15N-Tracertechnik in der Pflanzenbauforschung - Peschke, Heinz (Acta Agraria Debreceniensis, 2001)
Issues of nitrogen are still of particular importance in crop sciences. 15N-tracer are used to identify the N dynamics in soils and the N transfer between soil and plant. This tool is also helpful in clarifying fertilization problems. This article points out the special requirements for the application of stable 15N-isotops in agri-chemical research. Designs and results of selected laboratory experiments, examples of one-year field experiments, and a 15N long-term trial are represented in detail. The given literature refers to detailed results of diverse 15N publications in the system soil – fertilizer – (animal) – crop.